Pengembangan Sistem Manajemen Proyek dan Akun Hosting di Software House Berbasis Web (Studi Kasus Elecomp Software House) - Febiyana Nur Yahya; Achmad Arwan; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Elecomp Software house is a software development company in the city of Malang. Elecomp Software house accepts the creation of applications in the form of websites and mobile. In carrying out its daily activities, elecomp software house encountered several problems. These problems include the lack of integration of hosting account and domain data used in client-owned projects that are being worked on, domain payment reminder according to the time request from each client one by one, monitoring project progress that is still need manual work as well as revision of the project from the client and progress reporting that take a long time. The purpose of this research is to build a system that can integrate hosting account, domain and project data, remind domain payments to clients automatically, facilitate the distribution of resources and monitoring in project work, and can facilitate clients in monitoring and revising their projects. . This research was carried out using SDCL Waterfall as the method, and OOP or object-oriented programming as the design and programming method. After the system is finished, testing is done. There are three tests, unit tests on three methods that produce a total of 19 test cases, the test results are 100% passed. Integration testing resulted in 2 test cases, the results were 100% passed. Validation testing tests 78 functionalities and produces 115 test cases, the results are 100% valid.